Multi-Objective Reconfiguration of Radial Distribution Systems Using Reliability Indices - Paterakis, Nikolaos G.; Mazza, Andrea; Santos, Sergio F.; Erdinc, Ozan; Chicco, Gianfranco; Bakirtzis, Anastasios G.; Catalao, Joao P. S. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
This paper deals with the distribution network reconfiguration problem in a multi-objective scope, aiming to determine the optimal radial configuration by means of minimizing the active power losses and a set of commonly used reliability indices formulated with reference to the number of customers. The indices are developed in a way consistent with a mixed-integer linear programming (MILP) approach. A key contribution of the paper is the efficient implementation of the epsilon-constraint method using lexicographic optimization in order to solve the multi-objective optimization problem. After the Pareto efficient solution set is generated, the resulting configurations are evaluated using a backward/forward sweep load-flow algorithm to verify that the solutions obtained are both non-dominated and feasible. Since the epsilon-constraint method generates the Pareto front but does not incorporate decision maker (DM) preferences, a multi-attribute decision making procedure, namely, the technique for order preference by similarity to ideal solution (TOPSIS) method, is used in order to rank the obtained solutions according to the DM preferences, facilitating the final selection. The applicability of the proposed method is assessed on a classical test system and on a practical distribution system.
Keywords: Distribution system reconfiguration; epsilon-constraint method; loss minimization; mixed-integer linear programming; multi-objective optimization; reliability; LINEAR-PROGRAMMING APPROACH; NETWORK RECONFIGURATION; POWER-FLOW; OPTIMIZATION; REDUCTION; Engineering